2022
DOI: 10.1038/s41586-022-04507-5
|View full text |Cite
|
Sign up to set email alerts
|

Cortical ensembles orchestrate social competition through hypothalamic outputs

Abstract: How do we know our social rank? Most social species, from insects to humans, self-organize into social dominance hierarchies (1-4). The establishment of social ranks serves to decrease aggression, conserve energy, and maximize survival for the entire group (5-8). Despite dominance behaviors being critical for successful interactions and ultimately, survival, we have only begun to learn how the brain represents social rank (9-12) and guides behavior based on this representation. The medial prefrontal cortex (mP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 50 publications
0
56
2
Order By: Relevance
“…This connection could be a potential top down control on how the cortex impinges on the social behavior network thereby driving a preference. A similar circuit has been described during social dominance behavior (Padilla-Coreano et al, 2022). Whether this is mediated by the integration of multisensory cues has been left open.…”
Section: Mate Choice Decisionmentioning
confidence: 71%
“…This connection could be a potential top down control on how the cortex impinges on the social behavior network thereby driving a preference. A similar circuit has been described during social dominance behavior (Padilla-Coreano et al, 2022). Whether this is mediated by the integration of multisensory cues has been left open.…”
Section: Mate Choice Decisionmentioning
confidence: 71%
“…There is extensive literature on dominance and social hierarchy priming response to stress (Sapolsky, 2005), as it is known that hierarchical rank modulates the HPA system reactivity (Yohn et al, 2019), possibly due to higher-order impacts of the prefrontal cortex on hypothalamic function. Studies on stressful exposures modulating social dominance and hierarchical rank are less studied, but it has been reported that a cortico-hypothalamic circuit modulates social dominance (Padilla-Coreano et al, 2022) and maternal separation reduces adult dominance in a competition for water in water-restricted mice (Benner et al, 2014). Furthermore, chronic restraint decreases social dominance in the tube test (Park et al, 2018) and severe immobilisation stress heavily reduces social dominance in anxious mice (Lucion and Vogel, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies have shown that the synaptic efficacy regulated by AMPA receptors in this region controls the expression of social dominance (Wang et al, 2011), that the increase in social dominance as assessed in the tube test accompanies modifications of the stable actin fraction in synaptic spikes in this region (Tada et al, 2016), and that social dominance is followed by differential gene expression in this region (Pallé et al, 2019). Lastly, neuronal population activity in the mPFC predicts social rank and success in competitive settings (Padilla-Coreano et al, 2022).…”
Section: F1 Mrna Sequencing Does Not Show Overt Changes In Gene Expre...mentioning
confidence: 99%
“…Briefly, other studies measuring social dominance in rodents use a diverse set of methods to measure dyadic social relationships (22) through social conflict in a narrow tube (55,56) or competing for rewards (57), for example. While these tests are not guaranteed to correlate with home-cage behavior or one another (58,59), they provide further insight into the social relationship and can be used in a round-robin tournament to measure dominance relationships with equal numbers of social interactions.…”
Section: Agonistic Behavior and Social Dominance Relationshipsmentioning
confidence: 99%